RELATIONSHIP OF WORKING SHIFT WITH WORK FATIGUE IN PRODUCTION PART WORKERS IN PT X CIREBON CITY - Bayu Sela Priyatna (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2020)
work shift system is a way for companies to achieve production targets in meeting the increasingly rapid market demand, almost all industries implement a continuous production system so that companies impose work shifts, but with the implementation of work shifts it creates a work health problem that can affect the body's psychology, including fatigue. The purpose of this study was to determine the relationship between work shift and work fatigue in production workers. This research method using analytic observational with cross sectional study approach. The total population in this study were 76 workers in the production department at PT X Cirebon City, in taking work fatigue data using the Reaction Timer tool. Data analysis in this study used t-test and mann-whitney test. The results of this study for fatigue in the morning work shift there were 14 (38.9%) respondents experiencing mild fatigue while on the night shift there were 21 (58.3%) respondents experiencing mild fatigue and 5 (13.9%) moderate fatigue. From the bivariate analysis, it was found that there was a relationship between work shift and fatigue p = 0.001. Suggestions for companies to make SOP related to the prevention of work fatigue, 24 hours off after the shift.